Analysis of Prevalence, Risk Factor and Pharmacotherapy of Hypertension in Outpatients - MA, Khaled; Md, AsifAnsari; HA Md., Anwar (Indian Journal of Pharmacy Practice)
Objectives: To determine the prevalence, risk factors and the pattern of prescribing of antihypertensives in Abha. Methods: A survey of prevalence and prescribing pattern in patient with hypertension in primary care centres (Ballasmer General Hospital and Muhail General Hospital) of Abha, Kingdom of Saudi Arabia was conducted. Results: The data was collected from 2228 subjects and females constitute 53.09% of the population and the prevalence of hypertension was 64% in females (n=757) and 49.5% in males (n=517). Comorbidities were reported in 1274 patients including ischemic heart disease (27.2%), heart failure (10.2%), diabetes (21%) and hyperlipidemia (27.3%). Patients on mono therapy were treated with β-blockers (9% Vs 0 %), calcium channel blockers (0% Vs 10%), angiotensin-converting enzyme inhibitors (27.3% Vs 15%), and angiotensin II receptor blockers (0 % Vs 15%), diuretics (36.4% Vs 5%) and combination drug therapy (use of ≥ 2 antihypertensive drug classes) was highest in the Muhail General Hospital (55% Vs 27.3% in Ballasmer General Hospital). Conclusions: In conclusion it is evident from our study that hypertension is a common public health problem in Abha of Saudi Arabia, and is still on the rise and the pharmacotherapy of hypertension in patients in both hospitals were found in some instances not to conform to recommended guidelines and this warrant urgent attention along with modifiable risk factors such as physical activity and obesity to prevent hypertension.
Keywords: Hypertension; prevalence; risk factors